Biotic interactions mediate patterns of herbivore diversity in the Arctic. Issue 9 (19th May 2016) - Barrio, I. C.; Bueno, C. G.; Gartzia, M.; Soininen, E. M.; Christie, K. S.; Speed, J. D. M.; Ravolainen, V. T.; Forbes, B. C.; Gauthier, G.; Horstkotte, T.; Hoset, K. S.; Høye, T. T.; et al.
Abstract: Aim: Understanding the forces shaping biodiversity patterns, particularly for groups of organisms with key functional roles, will help predict the responses of ecosystems to environmental changes. Our aim was to evaluate the relative role of different drivers in shaping the diversity patterns of vertebrate herbivores, a group of organisms exerting a strong trophic influence in terrestrial Arctic ecosystems. This biome, traditionally perceived as homogeneous and low in biodiversity, includes wide variation in biotic and physical conditions and is currently undergoing major environmental change. Location: The Arctic (including the High Arctic, Low Arctic and Subarctic) Methods: We compiled available data on vertebrate (birds and mammals) herbivore distribution at a pan‐Arctic scale, and used eight variables that represent the most relevant hypotheses for explaining patterns of species richness. We used range maps rasterized on a 100 km × 100 km equal‐area grid to analyse richness patterns of all vertebrate herbivore species combined, and birds and mammalian herbivores separately. Results: Overall, patterns of herbivore species richness in the Arctic were positively related to plant productivity (measured using the normalized difference vegetation index) and to the species richness of predators. Greater species richness of herbivores was also linked to areas with a higher mean annual temperature. Species richness of avian and mammalian herbivores were related to the distance from the coast, with the highest avian richness in coastal areas and mammalian richness peaking further inland. Main conclusions: Herbivore richness in the Arctic is most strongly linked to primary productivity and the species richness of predators. Our results suggest that biotic interactions, with either higher or lower trophic levels or both, can drive patterns of species richness at a biome‐wide scale. Rapid ongoing environmental changes in the Arctic are likely to affect herbivore diversity through impacts on both primary productivity and changes in predator communities via range expansion of predators from lower latitudes.